Pengembangan Media Komik digital Untuk Mendukung Pembelajaran Di Era Digital Tingkat Sekolah Dasar - Syifa Dinda Syafira; Nazira Fauziah; Aji Iswanto; Zahra Febriannisa; Kheifa Azzahra Ansori; Sheila Ekasalwa N; Adi Abdurahman; Misbah Binasdevi (Academicus: Journal of Teaching and Learning, 2024)
This research is motivated by the learning process in grade 4, especially the subject of Islamic Religious Education, showing that the use of conventional media alone makes learning less interesting and less fun, so innovative and creative media is needed that can attract students' attention. This research aims to develop digital-based learning media such as digital comics, to support the teaching and learning process at SDN Palandakan 1. The research method used is a research and development method using the ADDIE development model involving the Analysis, Design, Development, Implementation, and Evaluation stages. The instruments used are observation, expert validation questionnaires and student responses and documentation. The data was analyzed using quantitative analysis with a percentage formula. The results of the feasibility test from the validation of material experts are 95% (very feasible), the validation of media experts is 93% (very feasible) which means that this digital comic media is feasible to be implemented in the learning process. Meanwhile, the student response received 80% results in the very satisfactory category. The results of the study show that the use of digital comics can improve the presentation of a fun atmosphere for students in the learning process in the classroom, especially the subject of Islamic Religious Education.